1-Alkyl-3-methylimidazolium 4-organyloxy-2, 3, 5, 6-tetrafluorophenyltrifluoroborates as a new platform for ionic liquids with specific properties. Issue 28 (20th March 2017) - Prikhod'ko, Sergey A.; Shabalin, Anton Yu.; Bardin, Vadim V.; Eltsov, Ilia V.; Shundrina, Inna K.; Parmon, Valentin N.; Adonin, Nicolay Yu.
Abstract : A new synthetic platform for ionic liquids (ILs) with specific properties was suggested based on the polyfluorophenyltrifluoroborate anions, Q[4-XC6 F4 BF3 ] (X = F, RO). Abstract : A new synthetic platform for ionic liquids (ILs) with specific properties was suggested based on the polyfluorophenyltrifluoroborate anions, Q[4-XC6 F4 BF3 ] (X = F, RO). Convenient preparative approaches to these ILs including the ones with chiral counteranions were developed. The dependence of physicochemical properties of ILs on the nature of substituents in the fluorinated ring was studied.